Tanbih al-'arif al-basir 'ala asrar al-hizb al-kabir lil-Imam al-Shadhili - Murtada al-Zabidi, Muhammad ibn Muhammad, 1732 or 3-1791; Jabarti, 'Abd al-Rahman, 1754-1822; Umrani, Abu al-Fadl Badr (Beirut : Al-Maktabah al-'Ilmiyah, 2003)
35